A novel diastolic dysfunction score: A proposed diagnostic predictor for left ventricular dysfunction in obese population - Kamelia, Telly; Rumende, Cleopas M.; Makmun, Lukman H.; Timan, Ina S.; Djauzi, Samsuridjal; Prihartono, Joedo; Fardizza, Fauziah; Tabri, Nur A. (Narra J, 2025)
Obesity-related diastolic dysfunction is an emerging contributor to heart failure and cardiovascular mortality. However, effective and accessible diagnostic tools are still limited. Current methods for assessing diastolic dysfunction are often invasive or technologically demanding, making them impractical for routine clinical use and community settings. The aim of this study was to develop a novel, non-invasive scoring system designed to predict diastolic dysfunction in obese adults, addressing this diagnostic gap. This community-based, prospective cross-sectional study was conducted in Jakarta, Indonesia, from March to November 2021, and included 82 participants aged 18 to 60 years, all with a body mass index (BMI) ≥25 kg/m². Patients with acute or critical illnesses, valvular heart diseases, or acute confusional states were excluded. Each participant underwent blood tests, polysomnography, and echocardiography. Of the study population, 80.5% were diagnosed with obstructive sleep apnea (OSA), and 12.2% exhibited diastolic dysfunction, all within the OSA group. The novel scoring system integrates four predictors: oxygen desaturation index (ODI) ≥39 (score 1; prevalence ratio: 4.31 (95% confidence interval (CI): 1.58–11.75)), HbA1C ≥5.95% (score 2; prevalence ratio: 6.32 (95%CI: 2.84–14.06)), pulmonary artery wedge pressure (PAWP) ≥10 mmHg (score 1; prevalence ratio: 5.95 (95%CI: 2.30–15.39)), and global longitudinal strain (GLS) ≥-16.95% (score 1; prevalence ratio: 4.32 (95%CI: 1.87–9.99)). A score of ≥2 predicted diastolic dysfunction with 90% sensitivity, with positive predictive value and negative predictive value of 40.91% and 98.33%, respectively. In conclusion, the diastolic dysfunction score is a simple and practical tool for the early detection of diastolic dysfunction in obese individuals without cardiovascular symptoms.